Repetition and content implications in advertising wear out: a practitioner’s view. - Kapexhiu, Kled (Advances in Social Sciences Research Journal, 2015)
One of the main advertisers’ dilemmas is: How long should their commercials or campaigns keep running? Repetition might enhance awareness, but too much exposure might diminish its effectiveness. The article examines theories that support the declining effectiveness of advertising over time, and suggests exposure and content strategies to advertisers. The literature review stresses that added repetition leads to greater and faster wear-out. Ease of processing, as a result of ad content, and resource availability speed up wear-out. The study suggests that along traditional effectiveness measures, advertisers should test their ads and campaigns for wear-in and wear-out. These tests should provide information on adverting and campaign longevity.